Jorge de Sena “no acaso de encontros tradutórios”: Petrarchan Echoes - Rossi, Elisa (2023)
From the 1980s onwards, a critical approach emerged seeking to consider the reflection on poetic translation in the light of the newborn concept of “intertextuality” (Kristeva, 1969), which could function as a “modified and more convenient perspective on a familiar object” (Koppenfels, 2010 [1985]: 5). In the wake of this proposal, a constellation of concepts has driven to an open and anti-dogmatic conception of translation, releasing it from normative categories and bringing it closer to other forms of “intertextual” dialogue, such as quotation, allusion or parody. The “consanguinity between translation and quotation” (Lourenço, 2021: 463) that characterizes Jorge de Sena’s work, with its pronounced intertextuality, calls for this kind of perspective. Among many possible examples, the forms of intertextual crossing (citational and translatory) with Petrarch’s work relate to a very personal critical reception of the author. Without considering translation as part of a broader dialogical system, it would not be possible to distinguish and understand the signs of an encounter that plays a relevant role in the construction of Sena’s poetic work.